Analisis Sistem Penjaminan Mutu Internal MTsN 4 Pasaman Barat - Aswar Anas (Al-Liqo: Jurnal Pendidikan Islam, 2022)
The most important issue of education is related to quality, especially since global surveys still place Indonesia in an unsatisfactory position. This condition makes the government have to think harder to advance education in this country. Efforts to improve quality have become a national priority, among others, by setting eight national standards, which can be measured through an internal quality assurance system. This study aims to see the achievement of SNP at the education unit level, in order to make improvements to the achievement of quality that is still low. The method used is a qualitative approach with survey and observation methods. The results showed that MTsN 4 Pasaman Barat achieved 86.03% of the SNP component. The standard of content is the highest standard of achievement, and the standard of infrastructure is the lowest standard that can be achieved. In addition, there are five standard sub-components that are below expectations, namely (1) the implementation of the learning process, (2) the competence of the head of madrasah, (3) ownership of complete and proper supporting facilities and infrastructure, (4) cross-subsidy services, and (5) the capacity of madrasah capacity. Through this research, it will be easier to determine the direction of improvement in the future.